A theoretical and experimental study of the viscous damping effect for diaphragm-based MEMS application - Tan, Chee Wee (2011)
In the analysis and design of microelectromechanical system (MEMS) devices, volume and surface forces are two physical quantities that are commonly encountered. During miniaturization, equal reduction of both the volume and the surface of a microstructure is not normally achievable. A 10% reduction in length results in the surface area. Therefore, the surface force effect of viscous damping has a more significant influence on the mechanical performance of MEMS devices such as frequency response characteristics, mechanical- thermal noise and switching speed.